Desarrollo e implementación de un sistema para la administración de: departamento de pesonal, material de guerra, material de intendencia y alimentación para el Grupo de Artillería No 1 "Bolívar" - Solano Pacheco, Tania Maritza (2014)
The present is consists of the development and implementation of a system for management: personnel department implements of war and war material supply for the Artillery Group 1 "Bolivar".